Lead poisoning in ancient Rome - Francois P. Retief; Louise Cilliers (Acta Theologica)
Lead was known to the ancients from at least the 4th millennium BC, but its use increased markedly during Roman times, to the extent that it became a health hazard. Mines and foundry furnaces caused air pollution; lead was extensively used in plumbing; domestic utensils were made of lead and pewter, and lead salts were used in cosmetics, medicines and paints. As a microbicide, lead was also used to preserve food. A grape juice concentrate (sapa) commonly used as a sweetener was prepared by preference in lead containers. Although Roman writers commented on the toxicity of lead, classic chronic lead poisoning was first described only in the 7th century AD. Skeletal lead content increased significantly in the Roman era, but peaked at a level only 41-47% of that of modern Europeans. The authors thus suggest that chronic lead poisoning did not contribute significantly to the fall of the Roman Empire in the West.